Pengaruh Leverage Dan Likuiditas Terhadap Nilai Perusahaan: Studi Pada Perusahaan Industri, Perdagangan, Jasa dan Investasi di BEI - Huatauruk, Rapat Piter Sony; Zalukhu, Rika Surianto; Colyn, Daniel (Accounting Progress, 2023)
This study aims to analyze the effect of leverage and liquidity on firm value. The dependent variable of the research is firm value (PBV), while the independent variables of the research are leverage (DAR) and liquidity (current ratio). The research was conducted among companies in the trading, services, and investment industries listed on the Indonesia Stock Exchange (IDX) in 2018. The research population was 145 companies. The research sample consisted of 104 companies. The sampling technique used was purposive sampling technique. This study uses secondary data. The data was analyzed using multiple linear regression analysis methods. The results of the analysis show that leverage has a negative and significant effect on firm value. While liquidity has a negative and insignificant effect on stock prices. Leverage and liquidity simultaneously have a significant effect on firm value.